Mycoplasma and Ureaplasma Infections in Transplantation: A Big Impact Despite the Lack of a Cell Wall - Schreiber, Peter W.; Müller, Nicolas (Emerging Transplant Infections, 2020)
In the general population, Mycoplasma spp. and Ureaplasma spp. are considered as pathogens with low virulence. Asymptomatic urogenital colonization with genital mycoplasmas is common. M. pneumoniae infections most frequently present as tracheobronchitis. In immunosuppressed individuals, a broad spectrum of invasive diseases has been attributed to these pathogens. After kidney transplantation and hematopoietic stem cell transplantation, Mycoplasma spp. and Ureaplasma spp. have been detected as causative pathogens in urogenital infections. Surgical site infections following solid organ transplantation are rarely caused by Mycoplasma spp. and Ureaplasma spp.. Recently, an association between hyperammonemia syndrome and genital mycoplasmas has been described after lung, kidney, and hematopoietic stem cell transplantation.

Distribution of Aspergillus Species and Prevalence of Azole Resistance in Respiratory Samples From Swiss Tertiary Care Hospitals - Ragozzino, Silvio; Goldenberger, Daniel; Wright, Patrick R; Zimmerli, Stefan; Mühlethaler, Konrad; Neofytos, Dionysios; Riat, Arnaud; Boggian, Katia; Nolte, Oliver; Conen, Anna; Fankhauser, Hans; Schreiber, Peter W; et al. (Open Forum Infectious Diseases, 2021)
Among 400 Aspergillus species from respiratory samples in Switzerland, Aspergillus fumigatus was the most frequent species. Non-fumigatus Aspergillus spp were more prevalent among solid organ transplant recipients and after azole exposure. Azole resistance was detected in 4 A fumigatus isolates, 3 of them with the “environmental” mutation TR34/L98H in the cyp51A gene.

Invasive Aspergillosis Due to Aspergillus Section Usti: A Multicenter Retrospective Study - Glampedakis, Emmanouil; Cassaing, Sophie; Fekkar, Arnaud; Dannaoui, Eric; Bougnoux, Marie-Elisabeth; Bretagne, Stéphane; Neofytos, Dionysios; Schreiber, Peter W.; Hennequin, Christophe; Morio, Florent; Shadrivova, Olga; Bongomin, Felix; et al. (Clinical Infectious Diseases: An Official Publication of the Infectious Diseases Society of America, 2021)
BACKGROUND: Aspergillus spp. of section Usti (A. ustus) represent a rare cause of invasive aspergillosis (IA). This multicenter study describes the epidemiology and outcome of A. ustus infections. METHODS: Patients with A. ustus isolated from any clinical specimen were retrospectively identified in 22 hospitals from 8 countries. When available, isolates were sent for species identification (BenA/CaM sequencing) and antifungal susceptibility testing. Additional cases were identified by review of the literature. Cases were classified as proven/probable IA or no infection, according to standard international criteria. RESULTS: Clinical report forms were obtained for 90 patients, of whom 27 had proven/probable IA. An additional 45 cases were identified from literature review for a total of 72 cases of proven/probable IA. Hematopoietic cell and solid-organ transplant recipients accounted for 47% and 33% cases, respectively. Only 8% patients were neutropenic at time of diagnosis. Ongoing antimold prophylaxis was present in 47% of cases. Pulmonary IA represented 67% of cases. Primary or secondary extrapulmonary sites of infection were observed in 46% of cases, with skin being affected in 28% of cases. Multiple antifungal drugs were used (consecutively or in combination) in 67% of cases. The 24-week mortality rate was 58%. A. calidoustus was the most frequent causal agent. Minimal inhibitory concentrations encompassing 90% isolates (MIC90) were 1, 8, >16, and 4 µg/mL for amphotericin B, voriconazole, posaconazole, and isavuconazole, respectively. CONCLUSIONS: Aspergillus ustus IA mainly occurred in nonneutropenic transplant patients and was frequently associated with extrapulmonary sites of infection. Mortality rate was high and optimal antifungal therapy remains to be defined.
Keywords: Aspergillus calidoustus; Aspergillus insuetus; Aspergillus pseudodeflectus; Aspergillus puniceus; Aspergillus ustus

Epidemiology and outcomes of bone and joint infections in solid organ transplant recipients - Pham, Truong‐Thanh; Andrey, Diego O.; Stampf, Susanne; Burkhard, Sara H.; Hirzel, Cédric; Tschopp, Johnathan; Ullrich, Kathrin; Strahm, Carol; Schreiber, Peter W.; Boillat‐Blanco, Noémie; Garzoni, Christian; Khanna, Nina; et al. (American Journal of Transplantation, 2022)

Do infectious diseases after kidney re-transplantation differ from those after first kidney transplantation? - Kusejko, Katharina; Neofytos, Dionysios; Van Delden, Christian; Hirsch, Hans H; Meylan, Pascal; Boggian, Katia; Hirzel, Cedric; Garzoni, Christian; Sidler, Daniel; Schnyder, Aurelia; Schaub, Stefan; Golshayan, Déla; et al. (Open Forum Infectious Diseases, 2024)
Abstract Background Infectious diseases (ID) are highly relevant after solid organ transplantation in terms of morbidity and mortality, being among the most common causes of death. Patients undergoing kidney re-transplantation (re-K-Tx) have been already receiving immunosuppressive therapy over a prolonged period potentially facilitating subsequent infections. Comparing ID events after re-K-Tx and first kidney transplantation (f-K-Tx) can delineate patterns and risks of ID events associated with prolonged immunosuppression. Methods We included adult patients with records on the f-K-Tx and re-K-Tx in the Swiss Transplant Cohort Study. We analyzed ID events after f-K-Tx and re-K-Tx within the same patients, and compared infection rates, causative pathogens and infection sites. Recurrent time to event analyses were performed for comparison of infection rates. Results A total of 59 patients with a median age of 47 years (range = 18 - 73) were included. Overall, 312 ID events in 52 patients occurred. In multivariable recurrent event modelling, the rate of ID events was significantly lower after re-K-Tx (HR = 0.70, p = 0.02). More bacterial (68.9% versus 60.4%) and fungal (4.0% versus 1.1%) infections were observed after f-K-Tx, but less viral infections (27.0% versus 38.5%) as compared to after re-K-Tx (p = 0.11). After f-K-Tx, urinary tract and gastrointestinal tract infections were more frequent; after re-K-Tx, respiratory tract and surgical site infections were more frequent (p < 0.001). Conclusions Infectious disease events were less frequent after re-K-Tx. Affected sites differed significantly after f-K-Tx compared to after re-K-Tx.